STRATEGI ORANG TUA DALAM MEMBIASAKAN ANAK MEMBACA Al- QUR’AN SETELAH KHATAM AL-QUR’AN DI KELURAHAN TIGO KOTO DI ATEH KOTA PAYAKUMBUH - Nurul Afifah; Fauzan Fauzan (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the problems found that after Khatam Al-Qur'an usually children rarely repeat reading the Qur'an either at home, mosque or prayer room. Then some parents pay less attention to their children in terms of reading the Qur'an. And also some parents do not provide an example in reading the Qur'an to their children. This type of research is a field research, namely qualitative research in which researchers observe and participate directly in the location where the data is located, whose data is obtained directly from the person being studied. The data collection techniques in this study were observation and interviews, the data analysis technique used was data reduction which selected the data first, after that display the data which after the data was selected, summarized and concluded and presented, then data verification, namely drawing conclusions from the data collected. has been analyzed, and the validity of the data technique used is by comparing the data from observations with data from interviews. Based on the results of the research that the author did, it is known that the strategy taken by parents to get their children to read the Qur'an after finishing the Qur'an is to pay attention to the child's ability to read the Qur'an, provide rules in read the Koran to children, then provide discipline in reading the Koran to children, then also give gifts when children are diligent in reading the Qur'an and give punishment when children are lazy to read the Qur'an. Keywords: Strategy, Parents, Children, Al-Quran, Khatam Al-Quran